The Role of Operational Cost Management in Improving Return on Assets (ROA) in the Hospitality Industry - Akbar Tarumanegara; Renny Yulia Bahren (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the role of Operational Cost Management (OPM) in improving Return on Assets (ROA) in the Indonesian hotel industry. Using a quantitative research approach, data were analyzed through simple linear regression using IBM SPSS Statistics version 26. The results showed that operational cost management has a positive and significant effect on ROA, with a p-value of 0.001 (<0.05). This finding implies that the more efficiently hotels manage their operational expenses such as labor, maintenance, and utilities the greater their ability to generate profits from total assets. Effective operational cost management improves asset utilization, strengthens financial performance, and enables hotels to maintain profitability despite fluctuations in occupancy rates and economic conditions. This study concludes that operational cost management is a strategic instrument for improving financial sustainability and achieving long-term competitiveness in the hotel sector.